(untitled) (Innovative professional education, 2023)
The article defines a progressive category of the population, which directly depends on the development of Ukraine during and after the end of martial law. The problematic issue of youth unemployment in Ukraine is raised in the complex conditions of the development of the modern economy, which are accompanied by daily changes in social and economic relations between the countries of the world. The advantages of youth entrepreneurship to ensure effective youth employment and the creation of new small businesses and additional jobs are emphasized. The practical component of the implementation of the issue of youth entrepreneurship during the training of qualified workers in professional (vocational and technical) education institutions is described.